Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Soal Jumping Task pada Materi Perbandingan Berdasarkan Gender - Ikhwani, Anggraini Dwi (Department of Mathematics Education , University of Jember, 2020)
This study aims to describe the critical thinking ability of male and female students in solving jumping task problems on proportion. The jumping task question used is a question with level C4 in Taksonomi Bloom. This type of research used is descriptive research with a qualitative approach. The data collection method used consisted of the documentation mathematics students report in the first semester, critical thinking test, and interviews. The subjects used in this study are 32 students of class VII G on SMPN 4 Jember. consists of 16 male students and 16 female students. The students are divided into three groups based on the mathematics students report in the first semester. The groups are high, medium, and low category mathematics ability. The results showed that male students with high category mathematics ability had TKBK 3 (critical), male students with medium category mathematics ability had TKBK 1 (less critical), male students with low category mathematics ability had TKBK 0 (not critical). While female students with high category mathematics ability had TKBK 3 (critical), female students with medium category mathematics ability had TKBK 2 (quite critical), female students with low category mathematics ability had TKBK 1 (less critical).